Banking Service Quality and Its Impact on Commercial Banks’ Reputation: An Applied Study at the University of Kerbala - Rassol Abd Aljalil Mahdi; Hayder Ali Abdullah; Mohammed Hussein Ali (Technium Business and Management, 2024)
The aim of the research is to determine the impact of banking service quality on the reputation of commercial banks due to the growth and development of banking services, while at the same time, the increase in problems faced by bank customers. The opinions of a group of affiliates at the University of Karbala, consisting of 80 affiliates representing the research sample, were taken. Their opinions were revealed according to the questionnaire model presented to them, which included 20 items distributed across two axes. The results obtained by the researchers through the answers of the research sample indicate the existence of a relationship, impact, and correlation between service quality and the reputation of commercial banks among the affiliates who domicile their salaries and the beneficiaries of the services of these banks.